New measure of consumer well-being for Indian car users - Manchanda, Rimple (Array, 2020)
Consumers today tend to look for material comfort and satisfaction from use and consumption of range of consumer durable goods, which are expected to induce consumer well-being. The current study investigates the consumer well-being of car users in Delhi and National Capital Region as this region has been recognized as biggest automobile market in India. Car industry is in the focus of the study because of its distinct features viz-aviz other consumer durable goods. The study is built around the existing conceptualization and measures of consumer well-being and intends to develop a separate measure of consumer well-being of car users in Delhi NCR through an exploratory research design. Three dimensional measure of consumer well-being has been developed.